A Study of Energy Conservation Using Green Cloud Computing - Kaushik, Ritu; Kakkar, M. (Indian Journal of Computer Science, 2019)
Cloud and green computing are rising areas in the IT field, both provide services to users and respond to their needs. Cloud computing is dependent on data whereas, green cloud computing is based on cloud framework. The use of cloud computing is increasing day by day which generates large amount of carbon dioxide because processing each request needs servers which consume high power energy and produce CO2. To reduce this some green computing techniques are required. These techniques use computer and memory devices and other devices like network communication devices for constructing a device that helps in reducing the effect of CO2 on the environment and making it green. This paper discusses some of the green cloud computing techniques and their future use.